2016
DOI: 10.1021/acs.est.6b00128
|View full text |Cite
|
Sign up to set email alerts
|

Microbial Sulfate Reduction Enhances Arsenic Mobility Downstream of Zerovalent-Iron-Based Permeable Reactive Barrier

Abstract: We assessed the potential of zerovalent-iron- (Fe(0)) based permeable reactive barrier (PRB) systems for arsenic (As) remediation in the presence or absence of microbial sulfate reduction. We conducted long-term (200 day) flow-through column experiments to investigate the mechanisms of As transformation and mobility in aquifer sediment (in particular, the PRB downstream linkage). Changes in As speciation in the aqueous phase were monitored continuously. Speciation in the solid phase was determined at the end o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 65 publications
(112 reference statements)
1
33
1
Order By: Relevance
“…The EDS qualitative analysis highlighted signals C, O, Al, Fe, Mn, and Si on the solid phase, in addition to small quantities of Zn in a range of 0.1-1%. These results are slightly different from Kumar et al [64], who used zero-valent iron to enhance sulfate reduction, but permeable reactive barriers. Silicon originates from the silica sand used as biomass at the initial stage of the treatment.…”
Section: Sludge Management With Nzvicontrasting
confidence: 94%
“…The EDS qualitative analysis highlighted signals C, O, Al, Fe, Mn, and Si on the solid phase, in addition to small quantities of Zn in a range of 0.1-1%. These results are slightly different from Kumar et al [64], who used zero-valent iron to enhance sulfate reduction, but permeable reactive barriers. Silicon originates from the silica sand used as biomass at the initial stage of the treatment.…”
Section: Sludge Management With Nzvicontrasting
confidence: 94%
“…Previous studies have shown that arsenic in solution could be removed through combination with sulfide minerals derived from microbial SO 4 2- reduction (Moore et al, 1988; Rittle et al, 1995; Kirk et al, 2004), and that the enhanced SO 4 2- reduction may be useful for arsenic remediation (Rittle et al, 1995; Newman et al, 1997; Castro et al, 1999; Macy et al, 2000; Jong and Parry, 2003; Lee et al, 2005; Saunders et al, 2005; Keimowitz et al, 2007; Saunders et al, 2008; Kirk et al, 2010; Luo et al, 2013). However, recently an experiment with permeable reactive barriers (PRB) was performed to test the effect of arsenic remediation in the presence microbial sulfate reduction, and found that up to 47% of total As initially present in the sediment was leached out in the form of mobile thio-As species (Kumar et al, 2016). Thus, more cautions should be taken on the geochemical behaviors of arsenic and sulfate in the environment (where the arsenite and arsenate have the potential to transform to mobile thioarsenates) when sulfate reducing bacteria are employed for arsenic remediation (Burton et al, 2014; Stucker et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The competition of different hydrogenotrophic bacteria normally leads to the formation of a redox sequence in which hydrogen oxidizing processes with a higher energy gain (e.g., sulfate reduction) preferentially proceed before others (e.g., methanogenesis or acetogenesis) by keeping the hydrogen concentration below a threshold. 18,22,80 However, with (initially) greater hydrogen production at a higher temperature and the subsequent increased hydrogen concentrations, either within or downstream of a PRB, redox processes, like sulfate reduction, methanogenesis, or acetogenesis, 16,18,20,21,80 as well as biodegradation, 22−24 are more likely to occur simultaneously or may even be enhanced. In real groundwater systems, with increasing temperatures, precipitation of iron(II) sulfides 16,18,81 by sulfate reduction could eventually occur due to various species of sulfate-reducing bacteria.…”
Section: ■ Environmental Implicationsmentioning
confidence: 99%